Participation in meaningful occupation : how do young adults living with cerebral palsy experience the quality of their participation? - Pieterse, Gisele Shaline (Stellenbosch : Stellenbosch University, 2013)
Thesis (MOccTher)--Stellenbosch University, 2013.